CdTe Quantum Dots Embedded in Multidentate Biopolymer Based on Salep: Characterization and Optical Properties - Ghasem Rezanejade Bardajee; Zari Hooshyar (Journal of Chemistry)
This paper describes a novel method for surface modification of water soluble CdTe quantum dots (QDs) by using poly(acrylic acid) grafted onto salep (salep-g-PAA) as a biopolymer. As-prepared CdTe-salep-g-PAA QDs were characterized by Fourier transform infrared (FT-IR) spectrum, thermogravimetric (TG) analysis, and transmission electron microscopy (TEM). The absorption and fluorescence emission spectra were measured to investigate the effect of salep-g-PAA biopolymer on the optical properties of CdTe QDs. The results showed that the optical properties of CdTe QDs were significantly enhanced by using salep-g-PAA-based biopolymer.